[Rezension von: Helen Hardacre, Shinto] - Andreeva, Anna (Bulletin of the School of Oriental and African Studies, 2018)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0041977X18000538/resource/name/firstPage-S0041977X18000538a.jpg